Association between dietary inflammatory index and inflammatory markers in the HELENA study. Issue 6 (22nd February 2017) - Shivappa, Nitin; Hebert, James R.; Marcos, Ascensión; Diaz, Ligia‐Esperanza; Gomez, Sonia; Nova, Esther; Michels, Nathalie; Arouca, Aline; González‐Gil, Esther; Frederic, Gottrand; González‐Gross, Marcela; Castillo, Manuel J.; et al.
Abstract : Previous research has shown that diet is associated with low‐grade systemic inflammation among adults. However, no study has yet been conducted to explore the association between inflammatory potential of diet and low‐grade systemic inflammation among adolescents whose dietary behavior may be different from adults. A pro‐inflammatory diet as evidenced by higher DII scores is associated with increased levels of various inflammatory markers in the healthy lifestyle in europe by nutrition in adolescents (HELENA) cross‐sectional study. Abstract : Background: Previous research has shown that diet is associated with low‐grade systemic inflammation among adults. However, no study has yet been conducted to explore the association between inflammatory potential of diet and low‐grade systemic inflammation among adolescents whose dietary behavior may be different from adults. Methods and Results: We examine the predictive ability of 24‐h recall‐derived dietary inflammatory index (DII) scores on inflammation among 532 European adolescents in the HELENA cross‐sectional study. The DII is a literature‐derived dietary index developed to predict inflammation. The DII was calculated per 1000 calories and was tested against C‐reactive protein, ILs‐1, 2, 4, 10, TNF‐α, ICAM, vascular cell adhesion molecule (VCAM), and IFN‐γ. All inflammatory markers had nonnormal distributions and therefore were log transformed. Analyses were performed using multivariable linear regression, adjusting for age, sex, city, BMI, smoking, and physical activity. Pro‐inflammatory diet (higher DII scores) was associated with increased levels of various inflammatory markers: TNF‐α, IL‐1, 2, IFN‐γ, and vascular cell adhesion molecule (bDIIt3vs1 = 0.13, 95% CI: 0.001, 0.25; 0.13, 95% CI 0.001, 0.25; 0.40, 95% CI: 0.03, 0.77; 0.53, 95% CI: 0.05, 1.01; 0.07, 95% CI: 0.01, 0.13, respectively). Conclusion: These results reinforce the fact that diet, as a whole, plays an important role in modifying inflammation in adolescents.